Object-to-Multidimensional database mapping algorithms - Lim, Tong; Lee, Sai (2003)
An object wrapper 3,4 is a piece of middleware that provides an object view on top of a legacy database management system. But legacy database management systems such as relational database systems (RDS) and multidimensional database systems (MDS) 5,6,7 are different in many aspects from an Object-oriented Data Model. Among these aspects are semantic management, data structures and data types supported in these models. As a result, it is crucial to understand these data models in order to design and implement an efficient piece of middleware. In this paper, a short discussion of the real-world data modelling requirements is presented. Then, this is followed by a discussion on an Object View's requirements. The third section of the paper presents the architecture of the Object-to-Multidimensional Mapping Engine (O-MME) 10,11,12,13,14,15,16,17,18,19. A detail discussion on major interfaces and classes in the Object-to-Multidimensional mapping algorithm are presented next. Issues such as data type conversion and database language statements generation are discussed in this paper also. Finally, some performance issues are presented and future possible researches are outlined.